Peningkatan Kemampuan Menulis Puisi Siswa Kelas XI SMA Negeri 1 Tanggetada Melalui Strategi Pemetaan Pikiran dalam Pembelajaran Berbasis Inquiry dan Learning Community Tahun Pelajaran 2022/2023 - Wayan Pageyasa (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The non-optimal ability to write poetry of high school students in class XI Negeri 1 Tanggetada in the 2022/2023 academic year can be seen from the initial observations which illustrate that the learning has not run optimally. To improve the ability to write poetry, teachers need to choose the right strategy, namely the mind mapping strategy. The data in this study were obtained from a poetry writing ability test and then analyzed descriptively. The description of the research results based on the initial observation of learning students are less active, easily bored, and students pay less attention to the teacher's explanation, so that the average student score is only 63 with 22% learning completeness. After the first cycle of action, the average value of students increased to 67 with 69% learning completeness. In cycle II, the results of the action showed that the mastery of the material after being given a test of students' poetry writing skills increased to an average of 78 with 94% learning completeness. Learning completeness with percentage calculations in cycle II has met the success indicators set in this study and the cycle is declared discontinued. The conclusion is that through the application of mind mapping strategy, it can improve students' poetry writing ability.